Invasive Candidiasis: Update and Current Challenges in the Management of This Mycosis in South America - Riera, Fernando Oscar (2022)
Invasive candidiasis encompassing Candida bloodstream infections and deep-seated candidiasis can become a persistent health problem. These infections are caused by Candida species and have high morbidity and mortality rates. Species distribution, access to diagnosis, treatment and mortality are different around the world. The mortality rate is high in South America (30–70%), and Candida albicans is the most prevalent species in this region. However, a global epidemiological shift to non-albicans species has been observed. In this group, C. parapsilosis is the species most frequently detected, followed by C. tropicalis, and at a slower rate, C. glabrata, which has also increased, in addition to the emerging C. auris, resistance to several drugs. This article summarizes relevant aspects of candidemia pathogenesis, such as the mechanisms of fungal invasion, immune response, and the impact of genetic defects that increase host susceptibility to developing the infection. We also discuss relevant aspects of treatment and future challenges in South America.